Application of Environmentally Friendly Natural Dyes from Raja Banana Stems (Musa sapientum), Kepok Banana (Musa acuminata) and Thin Skin Banana (Musa acuminata red dacca) on Batik Fabrics - Paryanto, Paryanto; Pranolo, Sunu Herwi; Fathika, Rahma N; Azizah, Rifo N; Wibowo, Angga Dwi (Dinamika Kerajinan dan Batik: Majalah Ilmiah, 2021)
Banana trees that are used as producers of natural dyes are plantains, thin skin bananas, and kapok bananas. The purpose of this study was to apply natural coloring agents from various types of banana stems such as Raja Banana, Kepok Banana,and Thin Skin Banana with various natural color pigments. Making natural dyes with stems banana and water solvent in a ratio of 1: 5. Color locking on a fabric with several fixators. Fixers used are alum (Al2 (SO4) 3), tunjung (FeSO4) and lime (CaCO3). Fabrics that have optimal fastness to washing with Gray Scale are fabrics with alum fixers and lime with grades 4-5 (Good). Fabrics that have color fastness to washing (Staining Scale) which are fabrics with alum fixers and chalk with a value of 5 (Very Good). Fabrics that have resistance to dry and wet rubbing are fabrics with alum fixers and lime with grades 4-5 (Good). Dyes on the plantain stems are sharper compared to the banana stems and thin skin banana stems, with reflectance values (R%) of 74.29.